Review Article Of 'Storied Island' - Will Derks (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
In her review of the book Traces of the Ramayana and Mahabarata in Javanese and Malay Literature in the journal Archipel edited by Ding Choo Ming and Willem van der Molen, Monique Zaini-Lajoubert clearly airs her amazement about the fact that the Introduction brings to the book “(…) n’explique pas pour quelle raison il ne se trouve aucun Malaisien ou Indonésien parmi les contributeurs, ni pourquoi les deux éditeurs sont également absent du volume”(p. 295). Zaini-Lajoubert is puzzled by the fact that the editors don’t explain why there are neither Malaysians nor Indonesians among the contributors, even though the book focuses on a region – characterized by extraordinary literary activity (“l’extraordinaire activité litteraire”) – where they live and work. Moreover, the editors themselves have not contributed to the book, except for the Introduction from which, incidentally, Ding Choo Ming is absent as well. It is not explained either, even though it was he who organized the conference on which this book is based. Hence, the Malaysian scholar who took the initiative for a scholarly gathering about Malay and Javanese literature, of which this book is the result, has left no trace in it. That is puzzling indeed.